The Correlation Between Neutrophil Lymphocyte Ratio And Length Of Stay Of COVID-19 Patients At Dr. Zainoel Abidin General Public Hospital Banda Aceh - Mutiawati, Vivi Keumala; Rifqi, Al-Abrar (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: Coronavirus disease 2019 or COVID-19 infection has showed an immunologic disregulation that could affect the clinical outcomes. Neutrophil lymphocyte ratio or NLR is one of inflammation marker that rapid and easily available at the initial moment of hospitalization. This study aimed to determine the correlation between NLR and length of stay of COVID-19 patients at Dr. Zainoel Abidin General Public Hospital Banda Aceh. Methods: This was an analitic retrospective study that observed medical records and complete blood count data of 577 COVID-19 hospitalized patients on January – March 2022 .The sample of this study was elected by purposive sampling and the sample size was 83 that obtained by lemeshow formula (1990). Result: The results showed that COVID-19 was dominated by male (53%) and 26 – 35 age group (19.3%). The value of NLR was dominated by ≥ 3.13 group (60.2%). The length of stay was dominated by ≤ 11 days group (69.9%). Bivariate analysis of this study was Spearman Rank test. The results of correlation test obtained p-value was 0.003 and r was 0.319. Conclusion: This study obtained that was a significant correlation between NLR and length of stay of COVID-19 patients at Dr. Zainoel Abidin General Public Hospital Banda Aceh.